The Role of Flavonoids as Potential Plant Fungicides in Preventing Human Carcinogenesis: A Short Communication - Katrin Sak (Pandawa Institute, 2023)
In the context of the steadily increasing prevalence of malignant disorders all over the world, identification of any novel possibilities for suppressing carcinogenesis is crucial leading to saving human lives. One of the important sources of exposure to potential carcinogens is food products which can be contaminated with different types of mycotoxins. These structurally diverse chemicals are produced by certain fungi, whereas many of them may be associated with the development of malignant neoplasms in distinct organ systems. In this perspective article, the ability of specific plant secondary metabolites from the class of flavonoids to suppress the release of carcinogenic mycotoxins from certain fungi, mostly the members of Aspergillus and Penicillium genera, is highlighted. This finding might support the development of novel flavonoid-based plant fungicides in the future, to lower the contamination of food products with mycotoxins and thereby also reduce the cancer prevalence in humans. In addition, the application of flavonoids as natural products instead of synthetic chemicals in plant cultivation is probably also more acceptable for final consumers, representing an actual step toward a greener future.